Kako uporabniki različnih strok zaznavajo uporabniško prijaznost vmesnikov sistemov za poizvedovanje - Vilar, Polona (Knjižnica, 2008)
The paper presents one part of a wider study, performed at the Department of LIS&BS at the Faculty of Arts in Ljubljana. The study investigated the perceptions of user friendliness of information retrieval systems' (IRS) interfaces and the role of individual characteristics of users in these perceptions. A user study with 61 postgraduate students of the University of Ljubljana was performed. Three interfaces were studied: Science Direct, Proquest Direct and Ebsco Host. Questionnaires and observation were used for data collection. The users' perceptions of importance of auxiliary functions, interface preference and perceptions of user friendliness of certain interface elements were investigated. Also, the connections between these perceptions and the users' individual characteristics were identified. Three sets of individual characteristics were included: approaches to studying, thinking styles and hemisphere leanings. In connection with the dimensions of individual characteristics very different user perceptions were expressed. Some dimensions of individual characteristics were also found to be connected to the users' academic areas. It is shown that the participants from different academic areas have different requirements and perceptions of user friendliness. The results of the study are relevant for the design of the user interfaces of disciplinary IRS. They also have implications for other areas, e.g. user education and training, acquisition and marketing.
Keywords: uporabniški vmesniki; sistemi za poizvedovanje; načrtovanje; zaznavanje; individualne značilnosti; hemisferičnost